1987
DOI: 10.1080/03610738708259317
|View full text |Cite
|
Sign up to set email alerts
|

Memory self-assessment and performance in aged diabetics and non-diabetics

Abstract: Non-insulin dependent diabetes in older adults is associated with elevated depression and a greater decline in certain aspects of cognitive functioning than is found with normal aging. This study sought to determine whether diabetics report more memory complaints in carrying out their daily activities, and if memory self-assessments are reflective of performance on laboratory tasks. Middle-aged (55-64 years) and old (65-74 years) diabetics and non-diabetic control subjects were studied. Results showed that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 14 publications
5
41
1
Order By: Relevance
“…Quite identical to previously reported data [1][2][3][4], we found diabetes to be associated with increased risk of cognitive impairment comparing healthy individuals. We evaluated the possible role of hyperinsulinemia in inducing dementia by comparing two drugs that differ in their mechanism of lowering blood glucose.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Quite identical to previously reported data [1][2][3][4], we found diabetes to be associated with increased risk of cognitive impairment comparing healthy individuals. We evaluated the possible role of hyperinsulinemia in inducing dementia by comparing two drugs that differ in their mechanism of lowering blood glucose.…”
Section: Discussionsupporting
confidence: 78%
“…Poor cognitive function is reported to be associated with Type 2 diabetes, although the etiology of this phenomenon is still unclear [1][2][3]. Comparing with non-diabetic individuals, the incidence of dementia in diabetic patients has increased about 50-100%, in both Alzheimer disease (AD) and vascular dementia [4].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 42 total studies, 3 (7%) did not provide enough information to be included in the OR or point prevalence calculations. Two of these three studies (32,33) reported only the statistical comparison of the mean depression scale scores of diabetic versus nondiabetic subjects, and the other (34) reported only lifetime rates of depression.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical and subclinical expressions of depression are present in Ͼ25% of patients with type 1 or type 2 diabetes (6)(7)(8)(9)(10)(11)(12)(13)(14) and have adverse effects on functioning and quality of life (15,16). The existing literature is not consistent and clear with regard to the association between depression and poor glycemic control.…”
mentioning
confidence: 99%